Non‐invasive prenatal diagnosis of single gene disorders by paternal mutation exclusion: 3 years of clinical experience. (20th May 2022) - Pacault, Mathilde; Verebi, Camille; Lopez, Maureen; Vaucouleur, Nicolas; Orhant, Lucie; Deburgrave, Nathalie; Leturcq, France; Vidaud, Dominique; Girodon, Emmanuelle; Bienvenu, Thierry; Nectoux, Juliette
Abstract: Objectives: Cell‐free fetal DNA (cffDNA) analysis is performed routinely for aneuploidy screening, RhD genotyping or sex determination. Although applications to single gene disorders (SGD) are being rapidly developed worldwide, only a few laboratories offer cffDNA testing routinely as a diagnosis service for this indication. In a previous report, we described a standardised protocol for non‐invasive exclusion of paternal variant in SGD. Three years later, we now report our clinical experience with the protocol. Design: Descriptive study. Setting: Multi‐centre French. Population: Indications for referral included pregnancies at risk of 25% or 50% of paternally inherited SGD, and pregnancies associated with an increased risk of SGD due to a de novo variant, either from strongly suggestive ultrasound findings or from a possible parental germinal mosaicism in the context of a previously affected child. Methods: Non‐invasive prenatal diagnosis was performed using custom assays for droplet digital PCR. Feasibility, diagnostic performance and turn‐around time were evaluated. Results: Mean time for a new assay design and validation was evaluated at 14 days, and mean result reporting time was 6 days. All referred pathogenic variants could be targeted except one located in a complex genomic region. A result was obtained for every 198 referrals except two. Conclusion: This service was successfully implemented as a routine laboratory practice. It has been widely adopted by French clinicians and patients for paternal variant exclusion in various disorders. Tweetable abstract: A robust approach to non‐invasive prenatal exclusion of paternal pathogenic variant in a diagnosis setting. Tweetable abstract: A robust approach to non‐invasive prenatal exclusion of paternal pathogenic variant in a diagnosis setting.